2017
DOI: 10.1103/physrevfluids.2.100501
|View full text |Cite
|
Sign up to set email alerts
|

Curvature capillary repulsion

Abstract: Directed assembly of colloids is an exciting field in materials science to form structures with new symmetries and responses. Fluid interfaces have been widely exploited to make densely packed ordered structures. We have been studying how interface curvature can be used in new ways to guide structure formation. On a fluid interface, the area of the deformation field around adsorbed microparticles depends on interface curvature; particles move to minimize the excess area of the distortions that they make in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…The effect of a static contact-line undulation, e.g., due to an irregular particle shape 14 or surface roughness, 23,24,30 is not our primary focus (although it is briefly considered in Appendix E). As was discussed in Section 2, such static undulations can produce a permanent capillary quadrupole (as well as higher multipoles 31,56 ) in the interface shape. Below, we focus only on the induced quadrupole.…”
Section: Particle With a Pinned Contact Linementioning
confidence: 93%
See 1 more Smart Citation
“…The effect of a static contact-line undulation, e.g., due to an irregular particle shape 14 or surface roughness, 23,24,30 is not our primary focus (although it is briefly considered in Appendix E). As was discussed in Section 2, such static undulations can produce a permanent capillary quadrupole (as well as higher multipoles 31,56 ) in the interface shape. Below, we focus only on the induced quadrupole.…”
Section: Particle With a Pinned Contact Linementioning
confidence: 93%
“…Colloids may create their own quadrupoles by virtue of their anisotropic shape, [12][13][14][15]52,53 surface chemistry, 3,4,54 or surface roughness. 23,24,30,31,[55][56][57] We refer to such distortions as permanent quadrupoles, following the terminology of Domínguez et al, 29 because they persist even in the absence of a background curvature. In the presence of a curvature gradient, an embedded particle with a permanent quadrupole moment experiences a lateral force F and transverse torque T. 58 Hu and Bush 59 famously showed that this coupling enables the larva of the waterlily leaf beetle to climb water menisci by simply adopting an arched body posture, which creates a quadrupolar deformation.…”
Section: Introductionmentioning
confidence: 99%
“…Surface heterogeneities and roughness distort the contact line at the nanoscale, but this is sufficient to induce capillary interactions between particles [76][77] [78], in the same way as curved menisci around anisotropic particles do [69].…”
Section: The Unexpected Key Importance Of Capillary Effects On Particmentioning
confidence: 99%
“…The bubble raft is formed by the buoyancy of the bubbles and macroscopic deformation of the meniscus. The phenomenon of capillary curvature attraction is now well established, in prior work it was reported how interface curvature influence an attraction of microparticles . An assembly of unmodified SiO 2 and amphiphilic Janus microbubbles showed strikingly different behaviors at a convex air–water interface .…”
mentioning
confidence: 93%